2019
DOI: 10.1093/jac/dkz237
|View full text |Cite
|
Sign up to set email alerts
|

Durability of different initial regimens in HIV-infected patients starting antiretroviral therapy with CD4+ counts <200 cells/mm3 and HIV-RNA >5 log10 copies/mL

Abstract: Objectives Our aim was to investigate the durability of different initial regimens in patients starting ART with CD4+ counts <200 cells/mm3 and HIV-RNA >5 log10 copies/mL. Methods This was a retrospective study of HIV-infected patients prospectively followed in the ICONA cohort. Those who started ART with boosted protease inhibitors (bPIs), NNRTIs or integrase strand transfer inhibitors (InSTIs), with CD4+ <200 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…Traditionally, InSTIs are combined with two nucleos(t) ide reverse transcriptase inhibitors in a three-drug regimen (3DR). The InSTI-based 3DRs have shown good efficacy and durability both in clinical trials [14,15] and in real-life settings [16][17][18]. Recently, dolutegravir, a last-generation InSTI characterized by a high genetic barrier, has been evaluated for the treatment of HIV infection in two-drug regimens (2DRs) with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, InSTIs are combined with two nucleos(t) ide reverse transcriptase inhibitors in a three-drug regimen (3DR). The InSTI-based 3DRs have shown good efficacy and durability both in clinical trials [14,15] and in real-life settings [16][17][18]. Recently, dolutegravir, a last-generation InSTI characterized by a high genetic barrier, has been evaluated for the treatment of HIV infection in two-drug regimens (2DRs) with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that starting ART with NNRTIs versus starting with bPIs; and starting ART with InSTIs versus starting with NNRTIs were less likely associated with treatment failure. Therefore, the durability of InSTIsbased regimen was longer than that of NNRTI-and bPI-based regimens [13]. The informations of percentage of STR uses were lack.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that starting ART with NNRTIs versus starting with bPIs; and starting ART with InSTIs versus starting with NNRTIs were less likely associated with treatment failure. Therefore, the durability of InSTIs-based regimen was longer than that of NNRTI-and bPI-based regimens [13]. The informations of percentage of STR uses were lack.…”
Section: Discussionmentioning
confidence: 99%